Asymmetric reactions of N-heterocyclic carbene (NHC)-based chiral acyl azoliums and azolium enolates - Zhao, Changgui; Blaszczyk, Stephanie A.; Wang, Jiaming (Green synthesis and catalysis, 2021)
N-Heterocyclic carbene (NHC) organocatalysis has been recognized as a powerful synthetic strategy for the construction of a wide variety of medicinally and biologically important molecules. Although NHCs are known as the umpolung of aldehydes, NHC-based species involving non-umpolung processes have attracted considerable attention over the past decade because of their diverse reactivity and applicability to asymmetric reactions. Previous reviews focused mainly on the reactions of α,β-unsaturated acyl azoliums, while the current review focuses on the generation and application of other NHC-based intermediates including α,β-unsaturated alkynyl acyl azoliums, dienyl acyl azoliums, azolium enolates, azolium dienolates, azolium allenolates, and cumulenol in asymmetric transformations since 2010. This review provided a brief synopsis of the use of NHC-based intermediates including higher order α, β-unsaturated acyl azoliums and azolium enolates for asymmetric transformations. The chemistry of these intermediates requires more investigation. In particular, transformations of alkynyl and dienyl acyl azoliums remain a formidable challenge. [Display omitted]